The preventive effect and mechanism of Tibetan medicine Aconitum tanguticum (Maxim.) Stapf on acute lung injury - Xiang Meng; Yu-Peng Liu; Jia-Wei Dai; Yuan Bai; Xin Hu; Muhammad Azhar; Xian-Ju Huang (Chinese Medicine)
Abstract Ethnopharmacological relevance Aconitum tanguticum (Maxim.) Stapf (ATS) is a rare Tibetan medicinal plant that belongs to the Ranunculaceae family. This herb is mainly distributed in the high-altitude areas of Qinghai, Gansu provinces, and Tibetan Autonomous Region in China. In Tibetan medicine, ATS is mainly used to treat lung inflammation, hepatitis, gastrointestinal diseases, influenza, fever caused by infectious diseases, food poisoning, snake and scorpion bites, and yellow water disease. ATS has anti-inflammatory, antiviral, and other pharmacological effects, according to recent research. It is welltolerated by individuals from diverse ethnic groups and has a long history of use in Tibetan medicine. Aim of the study This study investigated the preventive effects of ATS alcoholic extract on acute lung injury (ALI) in mice and aimed to elucidate its possible mechanism of action. Materials and methods Alveolar epithelial cells A549 and specific pathogen-free C57BL/6 mice were induced with lipopolysaccharide (LPS) to establish ALI models both in vivo and in vitro and to explore the pharmacological effects and therapeutic mechanisms of ATS. Results ATS down-regulated the mRNA levels of inflammatory factors NF-κB p65, TNF-α, IL-1β, and IL-8, inhibited the release of reactive oxygen species, inhibited epithelial-mesenchymal transition caused by sustained cell injury, promoted the Keap1/Nrf2/HO-1 signalling pathway, reduced the degree of oxidative stress in vivo, and inhibited the production of proteins associated with LPS-induced ferroptosis. Conclusion The Tibetan medicine ATS reduced pulmonary haemorrhage and oedema in ALI mice, alleviated the degree of lung tissue lesions, inhibited the expression of inflammatory factors and apoptosis, and plays a preventive role against acute lung injury in mice. Graphical Abstract